Learning Networks of Schools: The key enablers of successful knowledge communities - Katz, Steven; Earl, Lorna; Ben Jaafar, Sonia; Elgie, Susan; Foster, Leanne; Halbert, Judy; Kaser, Linda (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2008)
AbstractIn an effort to intentionally create the level of deep learning necessary for practitioners to make meaningful changes in their classrooms, professional networks are increasingly being promoted as mechanisms for knowledge creation that can makes a difference for students. This paper explores the way networks function by testing a theory of action within the Network of Performance Based Schools (NPBS) in British Columbia, Canada. It presents networks as collaborative systems that support particular ways of working and find expression within two distinct organizational units – the network itself and its participant schools.